Quantitative Assessment of Fat Levels in Caenorhabditis elegans Using Dark Field Microscopy. Issue 6 (1st June 2017) - Fouad, Anthony D; Pu, Shelley H; Teng, Shelly; Mark, Julian R; Fu, Moyu; Zhang, Kevin; Huang, Jonathan; Raizen, David M; Fang-Yen, Christopher
Abstract: The roundworm Caenorhabditis elegans is widely used as a model for studying conserved pathways for fat storage, aging, and metabolism. The most broadly used methods for imaging fat in C. elegans require fixing and staining the animal. Here, we show that dark field images acquired through an ordinary light microscope can be used to estimate fat levels in worms. We define a metric based on the amount of light scattered per area, and show that this light scattering metric is strongly correlated with worm fat levels as measured by Oil Red O (ORO) staining across a wide variety of genetic backgrounds and feeding conditions. Dark field imaging requires no exogenous agents or chemical fixation, making it compatible with live worm imaging. Using our method, we track fat storage with high temporal resolution in developing larvae, and show that fat storage in the intestine increases in at least one burst during development.